DETERMINAN PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA WANITA USIA SUBUR DI KELURAHAN BAKUNASE II - Kurniawati Benu; Masrida Sinaga; Enjelita M. Ndoen (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Breast self-examination (BSE) in women of childbearing age is one method of early detection of breast cancer that can be done by women. BSE is important because almost 85% of lumps in the breast can be found by the sufferer themselves, but there are still many women who do not understand what is BSE and how it is practiced to detect breast abnormalities. The general purpose of this study was to determine the determinants of BSE in women of childbearing age in Bakunase II. This type of research was quantitative with a cross-sectional study design. The research was conducted in Bakunase II village with a sample of 92 women of childbearing age. The data analysis used is univariate analysis and bivariate analysis with chi - square statistical test. The results of statistical tests showed that there was a relationship between knowledge (p-value 0.000), perceptions of the benefits of breast self-examination (p-value 0.031), perceived barriers to breast self-examination (p-value 0.045), perceived seriousness of breast cancer (p-valne 0.008), perceived susceptibility to breast cancer (p-value-0.008), and family support (p-value 0.000) with BSE behavior. It was concluded that the variables of knowledge, perceived benefit, perceived obstacles, perceived seriousness of breast cancer, perceived susceptibility to breast cancer and family support were related to BSE behavior in women of childbearing age in Bakunase II Village